Kesetaraan Gender Dalam Organisasi Badan Eksekutif Mahasiswa Keluarga Mahasiswa Universitas Mulawarman - Riska Riska; Marwiah Marwiah; Novita Majid (International Forum of Researchers and Lecturers, 2024)
The existence of gender equality within the organization of the Student Executive Board of the Mulawarman University Student Family which is seen based on reality and what factors influence the achievement of gender equality in the Ministry of Gender within the BEM KM Mulawarman University. This type of research is descriptive qualitative with research data sources of primary data and secondary data. The data analysis techniques used are data collection, data reduction, data presentation and drawing conclusions, and the theories used by the author are Gender theory by Edward Wilson and Feminism theory by Naomi Wolf. The results of this study explain that the reality of gender equality that occurs in the Mulawarman University BEM KM organization in the 2023/2024 BEM KM management has increased towards the involvement of women as leaders and in decision making. In addition, the factors that influence the achievement of gender equality in the gender ministry in the BEM KM organization at Mulawarman University can be seen based on the success and achievement of work programs carried out by the Ministry of Gender. These work programs encourage gender equality awareness and participation through education, empowerment, and overcoming barriers to achieving equality in the organization and ensuring that opportunities are effectively utilized by all parties.